Analysis of the effectiveness of BEL260 listening component in preparing students for MUET listening paper / Nurhadiana Nurulmatin - Nurulmatin, Nurhadiana (2014)
Malaysian University English Test (MUET) is compulsory to be taken by students to measure their level of English language proficiency. It is also the requirement for the admission into local universities. Since MUET was first launched in 1999, it helps in bridging the gap of the English language proficiency between the final year secondary school students and the requirement of tertiary level study. Thus, in order to provide adequate language preparation and needs related to tertiary education as well as to prepare students for MUET, the Academy of Language Studies in Universiti Teknologi Mara (UiTM) has taken the initiative of introducing Intermediate English (BEL260). Apart from reading, writing and speaking, BEL260 focuses on listening skill in preparation for MUET. However, the students are found to still have difficulty in performing well in the MUET listening component. Hence, this study, which involved 57 semester two Diploma students in UiTM Dungun, Terengganu was carried out to investigate the effectiveness of BEL260 listening component in preparing students for MUET listening paper. This was done by analysing the students' performances on each type of item tested in BEL260 listening test and MUET listening paper. The first and main finding suggests that BEL260 listening component did not help the students in preparing them for MUET listening paper. The second finding on MCQ items suggests that BEL260 listening component is the same level as MUET listening paper and it can be concluded that MCQ items in BEL260 listening test did help the students with MUET paper. In relation to Short Answer items, BEL260 listening component did not help students in the MUET listening paper as the students did not perform well in the Short Answer items. For Information Transfer items, many students did not do well for the items in MUET listening paper. The possible reason may be due to the fact that there is no formal lesson which stresses on Information Transfer items in BEL260 listening component. Feedbacks from students suggest that overall BEL260 listening component does not really help the students to prepare for the MUET listening paper. Suggestions from the students in relation to improving BEL260 listening component are to include the use of supplementary listening materials, conducive classroom environment and teaching and learning materials are to be improved. To further improve the BEL260 listening component, it is recommended that the Information Transfer items be included in order to better prepare students for the actual MUET paper. In addition, test taking strategies should be emphasized more as presently students are not given adequate exposure towards test taking strategies in the MUET listening paper. It is recommended for further studies to be done involving a bigger sample of students representing all the courses in UiTM Terengganu and also to involve the whole population of UiTM students from all branch campuses at large.